Is an alcoholic fixative fluid used for manual liquid-based cytology accurate to perform HPV tests? - Garbar C; Mascaux C; De Graeve P; Delvenne P (Dove Medical Press, 2011)
Christian Garbar1, Corinne Mascaux1, Philippe De Graeve2, Philippe Delvenne31Department of Biopathology, Institute Jean Godinot, Reims Cedex, France; 2Centre de Pathologie des Coteaux, Toulouse, France; 3Department of Pathology, University of Liege, Tour de Pathologie, Domaine Universitaire du Sart Tilman, Liège, BelgiumAbstract: In Europe, the alternative centrifuge method of liquid-based cytology is widely used in cervical screening. Turbitec® (Labonord SAS, Templemars, France) is a centrifuge method of liquid-based cytology using an alcoholic fixative fluid, Easyfix® (Labonord). It is now well accepted that the association of liquid-based cytology and human papillomavirus test is indissociable of cervical screening. The aim of this work was to demonstrate that Easyfix alcoholic fluid is reliable to perform Hybrid Capture® 2 (QIAGEN SAS, Courtaboeuf, France). In this study, 75 patients with colposcopy for cervical lesions served as gold standard. A sample was collected, at random, for Easyfix fixative cytological fluid and for Digene Cervical Sampler (QIAGEN). The results of Hybrid Capture 2 (with relative light unit >1) showed no statistical difference, a positive Spearman’s correlation (r = 0.82, P < 0.0001), and a kappa value of 0.87 (excellent agreement) between the two fluids. It was concluded that Easyfix is accurate to use in human papillomavirus tests with Hybrid Capture 2.Keywords: human papillomavirus, hybrid capture 2, Turbitec®, cervix cytology, liquid-based cytology